Captive broodstock development of common carp Cyprinus carpio Linnaeus, 1758: influence of age on spermatogenesis and fertilisation parameters - Betsy, C. Judith; Sampath Kumar, J. Stephen; Pon Jawahar, K. Thilak; Athithan, S.; Ahilan, B.; Karal Marx, K. (Indian Journal of Fisheries, 2016)
Knowledge on the quality of male and female gametes which may affect fertilisation success and larval survival is necessary to enhance fish production to meet global demand. Gamete quality is affected by factors like sex ratio, stocking density, age, size, nutrition and feeding regime. In the present study, the spermatological and fertilisation parameters as influenced by the age of brooders of Cyprinus carpio Linnaeus 1758 developed under captive condition from a single population were studied with special reference to dilution ratios. Milt was collected from 6, 12 and 18 months old brooders of C. carpio and diluted at three ratios viz., 1:40, 1:80 and 1:120 using freshwater fish saline. Sperm density, spermatocrit value, seminal plasma composition, motility duration, fecundity, fertilisation and hatching rates were studied for brooders of all age groups. The results showed that milt from 12 months old brooder produced good quality milt in terms of motility duration (69.66±4.72 sec), fertilisation rate (91.3±3.05%) and hatching rate (76.5±2.64%) at 1:40 dilution ratio.